2005
DOI: 10.1210/en.2004-1427
|View full text |Cite
|
Sign up to set email alerts
|

Apelin, a Newly Identified Adipokine Up-Regulated by Insulin and Obesity

Abstract: The results presented herein demonstrate that apelin is expressed and secreted by both human and mouse adipocytes. Apelin mRNA levels in isolated adipocytes are close to other cell types present in white adipose tissue or other organs known to express apelin such as kidney, heart, and to a lesser extent brown adipose tissue. Apelin expression is increased during adipocyte differentiation stage. A comparison of four different models of obesity in mice showed a large increase in both apelin expression in fat cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
725
11
23

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 794 publications
(809 citation statements)
references
References 38 publications
35
725
11
23
Order By: Relevance
“…This adipokine represent the the endogenous ligand of the orphan G protein-coupled receptor APJ, and is known to display a pro-angiogenic role [74]. The interest in apelin, which is expressed and secreted by adipose tissue both in mice and humans [75], has been generated by a study reporting that its levels were markedly increased in cirrhotic liver [76]. Apelin was found to be highly expressed by HSCs and in the same study the use of an antagonist of the apelin receptor was reported to inhibit not only angiogenesis but also hepatic fibrosis.…”
Section: Adipokinesmentioning
confidence: 99%
“…This adipokine represent the the endogenous ligand of the orphan G protein-coupled receptor APJ, and is known to display a pro-angiogenic role [74]. The interest in apelin, which is expressed and secreted by adipose tissue both in mice and humans [75], has been generated by a study reporting that its levels were markedly increased in cirrhotic liver [76]. Apelin was found to be highly expressed by HSCs and in the same study the use of an antagonist of the apelin receptor was reported to inhibit not only angiogenesis but also hepatic fibrosis.…”
Section: Adipokinesmentioning
confidence: 99%
“…The adipocyte expression of apelin was also found to be increased in rodent models of obesity and reduced in streptozotocin-induced diabetes as well as after fasting, and augmented by insulin, suggesting that insulin is an important regulator of apelin expression (12). Also circulating apelin levels were found to be increased in obesity (12).…”
Section: Introductionmentioning
confidence: 97%
“…It was recently reported that apelin is expressed in adipocytes (12), which suggests that apelin may function as an adipokine. The adipocyte expression of apelin was also found to be increased in rodent models of obesity and reduced in streptozotocin-induced diabetes as well as after fasting, and augmented by insulin, suggesting that insulin is an important regulator of apelin expression (12).…”
Section: Introductionmentioning
confidence: 99%
“…Apelin is derived from a larger precursor, preproapelin, the cDNA for which has been cloned in humans, cattle, rats and mice (Tatemoto et al, 1998). Plasma apelin is upregulated in rodents and humans during obesity, there is a strong relationship between adipocyte-secreted apelin and insulin levels (Boucher et al, 2005). In goats, feeding caused a slight increase in plasma apelin concentrations, and this increase was enhanced by water deprivation (Sato et al, 2012).…”
Section: Metabolic Hormonesmentioning
confidence: 99%